Natural immunity to evolutionary atavistic endotoxin in carcinogenesis induced by chemical agents (a hypothesis) - MONCEVIČIŪTĖ-ERINGIENĖ, Elena (Acta medica Lituanica, 2012)
A hypothesis of the possibility of natural immunity to evolutionary atavistic endotoxin in chemical carcinogenesis is proposed. Age-dependent stimulation of IgM class natural specific antibodies to the endotoxin of gram-negative bacteria Alcaligenes faecalis 415 (IgMNAE) was confirmed in the blood of normal adult rats. This phenomenon was also revealed in human population. Simultaneously, the suppression and subsequent stimulation of natural immunity to endotoxin under the effect of carcinogenic substances such as benzo(a)pyrene (BP) and metylcholanthrene (MCh) were determined in rats. At first, the primary age-related and the secondary carcinogen-induced enhancement of IgMNAE was explained as the compensatory reactions of the organism’s immune system. Later on, within the evolutionary resistance theory of the origin of cancer, based on the general biological laws (resistance to damage and atavism), which was formulated by the author in 2002–2005, another immunological IgMNAE enhancement mechanism was elucidated and explained by the possible activation of the dormant lipopolysaccharide molecules (atavistic endotoxin) alongside evolutionary resistance-related genes and oncogenes according to the inherited programme. All these mechanisms are transmitted from bacteria to mammal cells and possibly have an immense power to drive and control the process of carcinogenesis. It is the activation of these genes and their functions that helps the newly formed tumorous cells to revive the parasitic features in their unlimited division, invasiveness and metastatic growth. Its essence is a specific evolutionary response intended for the survival of damaged cells. Therefore, at present, there is a new oncological strategy problem – production of endotoxin-based vaccines and their application in cancer prophylaxis. IgMNAE can be undoubtedly helpful in elaborating new immunotherapeutic and diagnostic methods.